Intestinal Insights: The Gut Microbiome’s Role in Atherosclerotic Disease: A Narrative Review - Luana Alexandrescu; Adrian Paul Suceveanu; Alina Mihaela Stanigut; Doina Ecaterina Tofolean; Ani Docu Axelerad; Ionut Eduard Iordache; Alexandra Herlo; Andreea Nelson Twakor; Alina Doina Nicoara; Cristina Tocia; Andrei Dumitru; Eugen Dumitru; et al. (Microorganisms)
Recent advances have highlighted the gut microbiota as a significant contributor to the development and progression of atherosclerosis, which is an inflammatory cardiovascular disease (CVD) characterized by plaque buildup within arterial walls. The gut microbiota, consisting of a diverse collection of microorganisms, impacts the host’s metabolism, immune responses, and lipid processing, all of which contribute to atherosclerosis. This review explores the complex mechanisms through which gut dysbiosis promotes atherogenesis. We emphasize the potential of integrating microbiota modulation with traditional cardiovascular care, offering a holistic approach to managing atherosclerosis. Important pathways involve the translocation of inflammatory microbial components, modulation of lipid metabolism through metabolites such as trimethylamine-N-oxide (TMAO), and the production of short-chain fatty acids (SCFAs) that influence vascular health. Studies reveal distinct microbial profiles in atherosclerosis patients, with increased pathogenic bacteria (Megamonas, Veillonella, Streptococcus) and reduced anti-inflammatory genera (Bifidobacterium, Roseburia), highlighting the potential of these profiles as biomarkers and therapeutic targets. Probiotics are live microorganisms that have health benefits on the host. Prebiotics are non-digestible dietary fibers that stimulate the growth and activity of beneficial gut bacteria. Interventions targeting microbiota, such as probiotics, prebiotics, dietary modifications, and faecal microbiota transplantation (FMT), present effective approaches for restoring microbial equilibrium and justifying cardiovascular risk. Future research should focus on longitudinal, multi-omics studies to clarify causal links and refine therapeutic applications.